The Distribution of Onion Virulence Gene Clusters Among Pantoea spp. - Stice, Shaun P.; Shin, Gi Yoon; De Armas, Stefanie; Koirala, Santosh; Galván, Guillermo A.; Siri, María Inés; Severns, Paul M.; Coutinho, Teresa; Dutta, Bhabesh; Kvitko, Brian H. (Frontiers in Plant Science, 2021)
Pantoea ananatis is a gram-negative bacterium and the primary causal agent of center rot of onions in Georgia. Previous genomic studies identified two virulence gene clusters, HiVir and alt, associated with center rot. The HiVir gene cluster is required to induce necrosis on onion tissues via synthesis of a predicted small molecule toxin. The alt gene cluster aids in tolerance to thiosulfinates generated during onion tissue damage. Whole genome sequencing of other Pantoea species suggest that these gene clusters are present outside of P. ananatis. To assess the distribution of these gene clusters, two PCR primer sets were designed to detect the presence of HiVir and alt. Two hundred fifty-two strains of Pantoea spp. were phenotyped using the red onion scale necrosis (RSN) assay and were assayed using PCR for the presence of these virulence genes. A diverse panel of strains from three distinct culture collections comprised of 24 Pantoea species, 41 isolation sources, and 23 countries, collected from 1946-2019, were tested. There is a significant association between the alt PCR assay and Pantoea strains recovered from symptomatic onion (P<0.001). There is also a significant association of a positive HiVir PCR and RSN assay among P. ananatis strains but not among Pantoea spp., congeners. This may indicate a divergent HiVir cluster or different pathogenicity and virulence mechanisms. Last, we describe natural alt positive [RSN+/HiVir+/alt+] P. ananatis strains, which cause extensive bulb necrosis in a neck-to-bulb infection assay compared to alt negative [RSN+/HiVir+/alt-] P. ananatis strains. A combination of assays that include PCR of virulence genes [HiVir and alt] and an RSN assay can potentially aid in identification of onion-bulb-rotting pathogenic P. ananatis strains.